MADRASAH QUALITY IMPROVEMENT MANAGEMENT - Herman Susilo; Idham Kholid; Agus Pahrudin; Subandi Subandi; Koderi Koderi (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Based on the research results, Madrasah Tsanawiyah Negeri 1 Pesawaran and Madrasah Tsanawiyah Negeri 2 Pesawaran have implicitly implemented Total quality management, especially the concept of The Juran Trilogy as an effort to maintain and improve school quality. This is implemented through 1) Quality Planning, in the form of making a more comprehensive assessment guide that is adapted to Permendikbud No. 23 of 2016. 2) Quality Control, where the Principal always conducts monitoring and evaluation of programs that have been made, work assessments and joint evaluation meetings, and Carrying out Supervision of Program Activities. 3) Quality Improvement, namely by implementing class IX tutoring starting in January 3 times a week to increase the average score of the National exam, Implementation of extra-curricular English Club and providing opportunities for teachers to attend training, seminars, workshops, and others. In addition, by setting a permanent strategy to maintain and improve quality through a SWOT analysis in which the determination of the strategy is seen from the strengths, weaknesses, opportunities, and threats of strategies that can be suggested, namely (Sending Organization) (Strategy, Strength, and Threat) strategy, (Weakness- Opportunity) Strategies and (Weaknesses-Threats) strategies that are useful for formulating strategic plans for Madrasah Tsanawiyah Negeri 1 Pesawaran and Madrasah Tsanawiyah Negeri 2 Pesawaran to achieve the objectives of the key success factors.